#TITLE_ALTERNATIVE# - SITI NURAINUN (NIM 10204034), NYAYU
Lattice-gas automata model have been used to simulate the problems of kinetic theory of gas. Simulations have been made to determine velocity and speed distribution functions of two-dimension gas particles. Free expansion is selected as an example to show a gas performs a transition process from inequilibrium state to reach a final equilibrium state. When the gas system is in equilibrium, its speed and velocity distribution functions do not depend on time. For gas having enough low particle density and in equilibrium state, it yields Maxwell-Boltzmann distribution functions of velocity in x-direction which are Gaussian having average values about zero. In addition, these numerical experiments show Maxwell-Boltzmann speed distribution functions. For gas system that is far from equilibrium, its speed and velocity distribution functions do not satisfy Maxwell-Boltzmann distributions.